Using Illustrated Books with Surabayan Dialect to Promote Regular Child Dental Visits in East Surabaya Public Health Center - Kusumo, Aryo Dwipo; Setijanto, Darmawan; Berniyanti, Titiek; Hariyani, Ninuk; Sabdho Wening, Gilang Rasuna; Setiyowati, Dini; Palupi, Retno; Sosiawan, Agung; Ramadhani, Aulia; Amalia, Rovilla (Indonesian Journal of Dental Medicine, 2020)
Background: Previous research involving 100 children in the East Surabaya area reported a caries prevalence data of 89.5% with a Decayed, Missing due to carries, Filled Teeth index (DMFT) value of 5.42 (high category). In January–June 2018, only 373 out of 4,072 school-age children visited the Keputih Public Health Center. The dental visits were motivated out of dental health problems only. Parents, especially mother, should pay attention to their child's dental and oral health because they are in the primary tooth period, which will significantly affect the growth of their permanent teeth. Purpose: The illustration book in Surabayan dialect was the means to disseminate information on dental and oral health for children and parents, particularly mothers, to motivate regular dental visit and prevent dental caries. Methods: The parents received the illustrated book, and they were given some time to read and answer the questions. After that, the mothers were asked to assist their children in filling out the illustration book. The targets were improved understanding on the subject matter, which is dental and oral health, and to motivate the parents and children to have regular dental visit. Results: There was > 75% increase in understanding of the subject matter before and after the intervention. Conclusion: The intervention successfully improved the parents' understandings in the subject matter, and it was expected to motivate parents and their children to have regular dental visits in Keputih Public Health Center.